The features of use of training materials in educational process - Ayazbayeva, S.S.; Аkhmetzhanova, G.А.; Mikhaylova, N.B. (KSU Publ., 2016)
The article is devoted to the features of using teaching materials in studying foreign languages in the educational process. There were determined the problems of using teaching materials in foreign language lessons, specified the methods of using teaching materials that form ability to independently acquire knowledge, gather the necessary information, thus the key conditions for the effectiveness of this process is to give more opportunity for the teaching materials development. It was also revealed that one of the important features is the adaptation of learning materials depending on individual capabilities of students and their level of training, which further helps in forming communicative culture of the student contributes to his overall speech development and the expansion of horizons and raising of his feelings and emotions.
Оқу материалдарын оқу үрдісінде қолдану ерекшеліктері
Особенности использования учебных материалов в образовательном процессе
Keywords: Student; teaching materials; education; natural science; mechanical aids; contemporary schools; comprehensive; practical; supplementary readers; textbook